Hydrolytic and synthetic activities of esterases produced by Bacillus sp. A60 isolated from an oil contaminated soil - Loto, Flavia del Valle (2013)
A novel esterase producer strain named Bacillus sp. A60 was isolated from a soil sample contaminated with hydrocarbons. It was found to belong to Bacillus subtilis species through morphological, biochemical and 16S rRNA gene sequence analyses. This strain which can tolerate 15% (w/v) NaCl and growth at 55°C, produced an interesting esterase activity in Luria-Bertani medium. Two different molecular weight esterase activities were detected in zymographic assays. Culture supernatant and whole cells showed specific hydrolytic activities of 2.67 ± 0.11 U/mg of protein and 7.07 ± 0.09 U/mg of dry weight, respectively. Concerning ethyl acetate production, conversions of 88.00 ± 0 and 55.58 ± 0.78% were obtained with culture supernatant entrapped in polyacrylamine gel and whole cells, respectively. In addition, the effect of different concentration of LB medium components on both growth and extracellular esterase hydrolytic activity was also discussed.